ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI LOYALITAS KARYAWAN PADA PT. KARYA SWADAYA ABADI (KARSA) MEDAN - Purba, Betniar (Jurnal Manajemen dan Bisnis, 2017)
ABSTRACT The purpose of this research is to know and analyze the most factors Dominant influence employee loyalty PT. Karya Swadaya Abadi (Karsa) Medan, The number of samples is 70 respondents. Types of data used primary and secondary data, and methods of data collection through questionnaires and documentation, data analysis methods used factor analysis. From the results of the study and discussion, the number of KMO Measure of Sampling Adeguacy (MSA) was 0.851 with a significance level of 0.000, because the value of KMO above 0.50 and significant at 1 percent, then the data is feasible enough to be analyzed further by using factor analysis. The scree plot shows the graph, where from factor 1 to factor 2 (source line component number = 1 to 2), the direction of the line decreases quite sharply. Then from point 2 to 3, the line still decreases with the smaller slope. The fourth factor is already below the number of Y axes (eigenvalues). This shows that the three best factors to summarize the fourteen factors affecting employee loyalty at PT. Karya Swadaya Abadi (Karsa) Medan. The dominant factors affect employee loyalty PT. The work of Swadaya Abadi (Karsa) Medan with a correlation value greater than 0.80 consists of: incentives (0.823), status (0.821), and promotion (0.813). As for suggestions given as consideration to the leadership of the company is to increase employee loyalty, should the company hire the best performing contract employees to permanent employees. Instead, the company maintains incentives to employees who excel to increase employee loyalty to the company.